Dynamic Expression and Functional Implications of the Cell Polarity Gene, Dchs1, During Cardiac Development - Kathryn Byerly; Cayla Wolfe; Hannah Parris; Charlotte Griggs; Emily Wilson; Matthew Huff; Molly Griggs; Jordan Morningstar; Lilong Guo; Fulei Tang; Jan Guz; Taylor Petrucci; et al. (Cells)
Intercellular interactions among cardiac cell populations are essential for cardiac morphogenesis, yet the molecular mechanisms orchestrating these events remain incompletely understood. Dachsous1 (Dchs1), an atypical cadherin linked to mitral valve prolapse, is a core planar cell polarity protein whose function in the developing heart has not been fully elucidated. To address this, we generated a Dchs1-HA knock-in mouse model to define its spatial, temporal, and cellular expression patterns. Using immunohistochemistry, western blotting, and single-cell transcriptomics across developmental stages, we demonstrate that cardiac Dchs1 expression is restricted to non-cardiomyocyte lineages. DCHS1 displays dynamic subcellular localization and tissue organization depending on the developmental timepoint, with staining being found in epicardial and endocardial surfaces at earlier embryonic stages and in the compact myocardium in later fetal and neonatal stages. During fetal and neonatal stages, DCHS1-positive non-myocyte, non-endothelial cells form polarized extensions that bridge endothelial and non-myocyte, non-endothelial cells, suggesting direct heterotypic and homotypic interactions. Western blotting revealed evidence of DCHS1 proteolytic cleavage, with intracellular C-terminal fragments. RNA co-expression with its binding partner FAT4 supports a conserved, non-myocyte-specific DCHS1-FAT4 signaling axis. These findings identify DCHS1 as a potential molecular tether that is utilized in intercellular communications during cardiac development, with implications for congenital and acquired heart disease.